¿Existen migraciones verticales en el zooplancton de la Laguna de Los Padres? - Weigand, Paula (2008)
Diel vertical migration is a widely studied phenomenon occurring specially in marine and well stratified continental systems. The aim of this work was to study the spatial distribution of zooplankters in a «pampasic» shallow lake and to look for the existence of vertical migration. During summer 2002, replicated samples were taken during two 24 hintervals in the pelagic zone, using the 12 L Schindler-Patalas trap. Twenty-nine taxa were registered, corresponding 23 to Rotifera, 4 to Cladocera and 2 to Copepoda. The three groups considered in this work were generally located deeper when the water transparency was the highest. Maximum and minimum depths of residence were registered during light and dark hours, respectively. This probably indicates that changes in light could induce zooplankton movements. Although the vertical pattern observed in zooplankton populations from Los Padres Lake was similar to that of stratified lakes, with an ascending movement of individuals at dusk and a descending movement at dawn, it was not as pronounced as in deeper lakes. In order to obtain an explanation of the observed pattern, future work should deal with the description of spatial and temporal changes in abundance and availability of the resources.